Penerapan Metode Demonstrasi Dalam Pembelajaran Fiqh Materi Haji Bagi Siswa Kelas Viii Di Mts N Kepoh Delanggu Klaten Tahun Pelajaran 2016/2017 - Ni'mah, Khoiriyatun; , Drs. Najmuddin Zuhdi, M.Ag (2017)
education is the important lesson for students. The student required to understand and can be the master for the Islamic education lesson. Islamic education is important curriculum to applied start elementary school until college. One of Islamic education lesson is Fiqh. Fiqh is the difficult material, the material included about praying, fasting, tithe, jinayah, hajj, umrah, etc. This material must be teach for all of students. To avoid misunderstanding and to make the study clear, the researcher limits the problem on describing the process of teaching Fiqh. The researcher focused on chapter Hajj only and will be discuss about the application of demonstration method in teaching learning chapter Hajj for eighth grade students of MTs N Kepoh Delanggu in Klaten in the academic year 2016/2017. The problem from this research why the application of the methods is demonstration in chapter Hajj for eighth grade students of MTs N Kepoh Delanggu in Klaten? and is what the application of demonstration method can improve understanding and increase the student‟s scoring in chapter Hajj for eighth grade students of MTs N Kepoh Delanggu in Klaten in the academic year 2016/2017?. The objectives of this research is to know the application of methods of demonstration in chapter Hajj for eighth grade students of MTs N Kepoh Delanggu in Klaten and to know the application of demonstration method can improve understanding and increase the student‟s scoring in chapter Hajj for eighth grade students of MTs N Kepoh Delanggu in Klaten in the academic year 2016/2017. The benefit of the research can develop of knowledge, especially the application of demonstration method and can give contribution to the improvement of the understand teaching learning process in chapter Hajj. The design of the research is classroom action research. Based on the research background above, the subject of the study is limited to the eighth grade students of MTs N Kepoh Delanggu in Klaten in the academic year 2016/2017. The researcher collecting the data from the observation, test, and documentation. The research findings in this research shows that, the application of demonstration method can improve understanding and increase the student‟s scoring. It seen from post test results from each cycle that are cycle I (56,52%), cycle II (86,95%) and the achievement student‟s scoring which realize score of KKM.